Pengaruh Penambahan Tepung Daun Kelor pada Ransum terhadap Kandungan Nutrisi dan Fisik Telur Itik - M. Indriati; E. Yuniarsih (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The aim of this study were to analyzed effect of adding Moringa leaf meal on feed in egg quality of duck.The livestock used were 27 ducks with 3 treatments and 3 replication and each replication there were 3ducks. P0 (feed + 0% Moringa), P1 (feed + 5% Moringa) and P2 (feed + 10% Moringa). Experimentaldesign used completely randomized design. Variables observed in this study were physical quality such asegg weight and yolk color score and chemical quality such as cholesterol and protein level. Observationwas carried out after 4 weeks of feed treatment. Significantly different result were seen in egg weightvariables (P<0.05), treatment of 5% and 10% moringa leaf in feed significanty decrease weight of eggs.Adding 5% and 10% moringa leaves increased a yolk color score, respectively 7.11 + 1.05 and 7.44 +0.52 compared with control 6.55 + 3.20. Cholesterol levels decrease in 5% feed treatment 14.07 + 2.07compared to control 15.46 + 1.43. The adition of 5% and 10% moringa leaves increased protein level10.90% and 10.86% respectively, compared to control 10.74%. However, base on statistical analysis ofyolk color score, cholesterol and protein levels were not significantly different (P>0.05).